Scheduling Information System at SMA N 1 Madang Rasuan OKU Timur - Kurniawan*, Dedy; Passarella, Rossi; Sutarno, Sutarno; Rifai, Ahmad; Isnanto, Rahmat Fadli; Ubaya, Huda; Exaudi, Kemahyanto; Sari, Purwita; Hanifah, Izzati Millah; Perdani, Tharisa Antya (Universitas Lancang Kuning, 2024)
The development of technology and information systems is currently so rapid, especially after the corona pandemic era, everything began to use technological assistance, not spared until the elements of the school were required to use technology as a means of learning, one of the considerations of the school in using technology including as a schedule management system. In this website-based scheduling application system for SMAN 1 Madang Suku 1, the author and co-author create a scheduler application that can easily manage schedules that already have integrated data between subjects, teachers, majors, classes at school. the purpose of making this application system is to increase efficiency in the process of scheduling classes and rooms at SMA 1 Madang Rasuan OKU Timur, and also make it easier for students to access the required schedule so that the schedule does not have to be taken at school again. The final result of this research is to produce a web-based application program that can help teachers or school admins to create and manage subject schedules with a good appearance and equipped with various features so that the subject scheduling process becomes more efficient and organized.